PERSEPSI MAHASISWA YANG MENGHAMBAT ADOPSI INOVASI BENTUK KEGIATAN PEMBELAJARAN MAGANG MERDEKA BELAJAR KAMPUS MERDEKA - Budhi Waskito; Noning Verawati; Hanindyalaila Pienrasmi (Jurnal Perspektif Pendidikan, 2022)
The number of students in the seventh semester of the Communication Science Major at the University of Bandar Lampung (PSIK-UBL) who decided to adopt an innovation in internship activity as one of the projects in learning activities at Merdeka Belajar Kampus Merdeka Program (BKP Internship MBKM innovation) in the odd semester of 2021/2022 was very low, at the amount of 12.5 percent. This study aims to analyze student’s perceptions that hinder the adoption of MBKM Internship BKP innovations. The design of this research is a qualitative research with a case study approach. The research informants were 7th semester students of PSIK-UBL who decided not to adopt the MBKM Internship BKP in accordance with the major’s curriculum. The collecting data was done through focus group discussions and in-depth interviews. Data analysis was done descriptively. The results showed that student’s perceptions that hindered the adoption of MBKM Internship BKP innovations at PSIK-UBL in the odd semester 2021/2022 were MBKM Internship BKP project inhibited students to graduate on time, MBKM internship’s cost more out compared to regular internships, the requirement of partnership agreement document was considered complicated, high risk of not passing the MBKM internship, there is no proof yet that can be seen from the result implementation of the MBKM internship for students.